Self-interest or altruism: Entrepreneurs’ military experience and the motivation of corporate philanthropic donations - Chen, Huaichao; Wu, Huichao; Li, Haiting (Frontiers in Psychology, 2022)
This study aims to explore the motivation of corporate philanthropic donations through investigating the impact of entrepreneurs’ military experience. Based on the data from the 12th Chinese privately owned enterprises survey, this study finds that entrepreneurs’ military experience has a positive impact on corporate philanthropic donations and the result keeps consistent after a series of robustness tests. Further, corporate financing constraints do not significantly influence the relationship between entrepreneurs’ military experience and corporate philanthropic donations, while return on equity (ROE) strengthens the relationship. Therefore, entrepreneurs with military experience still donate even if their firms suffer from financial constraints. When firms achieve higher ROE, they will donate more. The findings suggest that the donations of firms with military entrepreneurs are more likely to be altruistic, enriching the understanding of the motivation of corporate philanthropic donations.